A Smart Contract Framework for Project Financing in Gold Mining Operations: Implications for Improved Financial Forecasting - Priskilla, Silvia Lydia; Berawi, Mohammed Ali; Sari, Mustika, Dr. (Smart City, 2026)
Gold mining projects are characterized by high capital intensity and significant operational variability, making financial forecasting particularly sensitive to the quality and timing of cash-flow data. In practice, conventional financing systems rely on multi-stage administrative processes that create delays between work completion and payment realization, reducing the reliability of financial records used for investment evaluation. This study aims to develop a smart contract-based financing framework to improve the accuracy of profitability projections in gold mining projects. A case study approach is employed using operational and financial data from a mining project in Sumatra over the period 2023–2026. The analysis combines archival data evaluation, expert survey, and financial simulation using Net Present Value (NPV) as the primary performance indicator. The results show that the existing system generates payment delays of approximately 28–30 days, contributing to unstable cash-flow patterns. By implementing a smart contract mechanism, verification time can be reduced by 30–60%, resulting in approximately 25% improvement in cash-inflow timing. Although total revenue remains unchanged, the earlier realization of cash flows leads to an increase in NPV from USD 114.07 million under the conventional system to between USD 115.01 million and USD 118.41 million, representing an improvement of up to 3.81%. These findings demonstrate that improvements in financial performance are not solely dependent on increasing production or revenue but can also be achieved by optimizing the timing and reliability of financial transactions. The proposed framework highlights the potential of smart contract-based systems to enhance both operational efficiency and financial accuracy in complex project environments.